A kind of microcrystalline glass and preparation method thereof
By reasonably combining high alumina, zirconium and zinc and crystallization, specific crystal particles are formed, the problem of insufficient strength and hardness of existing high alumina glass is solved, and microcrystalline glass with high strength, hardness and high-quality signal transmission is achieved.
Patent Information
- Application Number
- CN201910529369.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-06-19
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2039-06-19
AI Technical Summary
The strength and hardness of existing high-aluminum glass are not high enough to meet the high mechanical strength and high chemical temperature requirements of protective cover plates and screen patch materials.
By reasonably combining high aluminum, zirconium and zinc, the glass is crystallized to form crystal particles such as cordierite, tetragonal zirconia and zinc spinel, thereby improving the hardness and strength of the glass.
It has achieved high-strength and high-hardness microcrystalline glass with a Mohs hardness of 6.8-7.8, which can maintain high-quality signal transmission at high temperatures and has good thermal stability and light transmittance.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass and relates to a microcrystalline glass and a preparation method thereof. Background Art
[0002] With the gradual popularization of mobile phones, computers, etc., and the wide application of various other devices with touch screen panels in various industries, the demand for corresponding protective covers and screen patches has greatly increased. Generally, the materials used to process these protective covers and screen patches need to meet the requirements of high mechanical strength, high Young's modulus, high chemical temperature resistance, and lightness and thinness. Ordinary soda-lime glass cannot meet these requirements, and even after chemical strengthening, its performance is still difficult to meet the requirements.
[0003] Most existing technologies use high-aluminum glass as the material for processing protective cover plates and screen patches, in which the content of aluminum oxide Al2O3 is about 18%. Due to the high aluminum oxide content, the strength of high-aluminum glass is higher than that of ordinary soda-lime glass, and its ion exchange capacity is also stronger, but its strength and hardness still cannot meet actual needs.
[0004] Therefore, it is of great significance to study a glass with high strength and high hardness. Summary of the invention
[0005] The purpose of the present invention is to solve the problem that the strength and hardness of high-aluminum glass in the prior art are not high enough, and to provide a microcrystalline glass and a preparation method thereof. The present invention adopts a reasonable combination of high aluminum, high zirconium and high zinc, and crystallizes the glass without chemical tempering, thereby achieving high strength and high hardness, and also meeting the high-quality transmission requirements of signals.
[0006] To achieve the above object, the scheme adopted by the present invention is as follows:
[0007] A method for preparing microcrystalline glass, wherein a mixture is cast into glass and then subjected to crystallization treatment to obtain the microcrystalline glass, wherein the mixture mainly consists of 40-60wt% SiO2, 22-32wt% Al2O3, 2-9wt% MgO, 3-10wt% ZnO and 4-10wt% ZrO2, and the crystallization treatment is divided into two stages, the temperature of the first stage (i.e., nucleation temperature) is 680-780°C, and the time is 1-4h, and the temperature of the second stage (i.e., crystallization temperature) is 920-980°C, and the time is 1-3.5h. The first stage is mainly a nucleation stage, and the second stage is a crystallization stage. The temperature and time of the two stages of the crystallization treatment should not be too high, otherwise it will result in the inability to form crystals, or the formed crystal particles are too large, and the microcrystalline glass becomes brittle.
[0008] The invention adjusts a reasonable proportion of the components of the mixture, controls the crystallization temperature and the crystallization time, and finally forms a crystal structure in which the particles are evenly distributed in a dendrite shape, thereby greatly improving the hardness and strength of the glass; the mixture is mainly composed of 40-60wt% SiO2, 22-32wt% Al2O3, 2-9wt% MgO, 3-10wt% ZnO and 4-10wt% ZrO2, MgO, Al2O3 and SiO2 cooperate with each other to form cordierite crystal particles with a hardness of 7-7.5 on the Mohs scale through crystallization treatment, ZrO2 cooperates with each other to form tetragonal zirconia crystal particles with a hardness of 8-8.5 on the Mohs scale through crystallization treatment, and ZnO, Al2O3 and MgO cooperate with each other to form zinc spinel crystal particles with a hardness of 7.5 on the Mohs scale through crystallization treatment, and the content of each component in the mixture is the best range for the formation of the three crystal particles. The temperature and time of the crystallization treatment are regulated so that the microcrystals have specific types, quantities and sizes, and finally a transparent microcrystalline glass is obtained, which has the dual characteristics of glass and ceramics. The atomic arrangement inside ordinary glass is irregular, so ordinary glass is fragile. Microcrystalline glass, like ceramics, is composed of crystals, and the atomic arrangement is regular, so microcrystalline glass has stronger toughness than ordinary glass. For high-zirconium and high-aluminum glass, its own strength and hardness are relatively high. After the crystallization treatment, the microstructure of the glass changes, generating crystal particles, and its hardness and strength are greatly improved. In the prior art, most of the glass used for the back panel of the mobile phone is ordinary high-aluminum glass, not microcrystalline glass. The aluminum oxide content of ordinary high-aluminum glass is usually less than 20%, and it must be chemically tempered to achieve the initial use strength and hardness.
[0009] As a preferred solution:
[0010] As described above, the preparation method of microcrystalline glass, the mixture also contains 0-5wt% B2O3, 0.1-1wt% Y2O3, 0.1-0.8wt% Sb2O3, 0-10wt% BaO, 0.2-2wt% La2O3 and other components with a content of less than 1.5wt%, the addition of Y2O3 lowers the melting point of ZrO2, the addition of Sb2O3 is beneficial to the clarification of the glass, the addition of La2O3 is beneficial to improve the refractive index and strength of the glass, and the other components are used as nucleus agents and auxiliary raw materials.
[0011] As described above, a method for preparing microcrystalline glass comprises the following steps of: melting the mixture at a temperature above 1658°C for more than 8 hours and then casting or pressing the mixture into shape. The casting temperature and time should not be too small, otherwise it will easily lead to uneven melting of the mixture and the microcrystalline glass will easily form stress and break.
[0012] In the method for preparing microcrystalline glass as described above, an annealing treatment is performed after the crystallization treatment. The annealing temperature is 600-700° C. The annealing time is determined according to the size of the product. The purpose of the annealing treatment is to eliminate the structural stress of the product.
[0013] The microcrystalline glass prepared by the preparation method of microcrystalline glass as described in any of the above items is mainly composed of a glass matrix and crystal particles dispersed therein in a dendritic distribution, and the crystal particles are composed of cordierite crystal particles, tetragonal zirconia crystal particles and galvanneal crystal particles. The particle sizes of the cordierite crystal particles, tetragonal zirconia crystal particles and galvanneal crystal particles change from nanometer scale to micrometer scale depending on the crystallization time and crystallization temperature, and the glass also changes from transparent to ceramic. The Mohs hardness of the glass gradually increases from 6.0 to a maximum of 7.8.
[0014] The microcrystalline glass as described above has a Mohs hardness of 6.8 to 7.8, which can reach above 7.0 while ensuring transparency, which is sufficient to meet the needs of daily life. The Mohs hardness of the high-aluminum glass in the prior art is about 6.0. The microcrystalline glass with a thickness of 0.5 mm is not broken after being impacted by a steel ball weighing 50 g and falling freely from a height of 1.5 m.
[0015] As described above, the maximum light transmittance of the transparent microcrystalline glass with a thickness of 4 mm is 80-92%, and the wavelength of the light is 400-800 nanometers. The existing technologies including Japan's Ohara and Germany's Schott microcrystalline glass cannot reach this level. The high light transmittance provides a guarantee for the subsequent color spraying, the brightness of the coating and the transmission of signals.
[0016] As mentioned above, the expansion coefficient α of the microcrystalline glass at a temperature of 30°C is 34*10 -7 ~36*10 -7 / ℃, the expansion coefficient of high aluminum glass in the existing technology under the same temperature conditions is 84*10 -7 / ℃, the expansion coefficient of Japanese microcrystal is 91*10 -7 / ℃.
[0017] Beneficial effects:
[0018] (1) A glass-ceramic of the present invention has good thermal stability and high light transmittance;
[0019] (2) The microcrystalline glass of the present invention has high hardness and strength, with a Mohs hardness of 6.8-7.8 and an impact strength of 1500 mm high 50 g steel ball impacting a 0.5 mm plate without breaking;
[0020] (3) The microcrystalline glass of the present invention has good forming performance and does not lose transparency during 3D hot bending;
[0021] (4) A method for preparing microcrystalline glass of the present invention has better chemical stability and other properties after compounding multiple crystal phases, and no chemical tempering treatment is required;
[0022] (5) The preparation method of the microcrystalline glass of the present invention is simple and has great promotion value. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0024] Example 1
[0025] A method for preparing glass-ceramics comprises the following steps:
[0026] (1) melting the mixture at a temperature of 1658° C. for 8.3 hours and then casting or pressing the mixture to obtain ordinary glass, wherein the mixture consists of 41.8 wt % SiO2, 30 wt % Al2O3, 9 wt % MgO, 3.8 wt % ZnO, 5.8 wt % ZrO2, 3.2 wt % B2O3, 0.6 wt % Y2O3, 0.3 wt % Sb2O3, 2.5 wt % BaO, 2 wt % La2O3 and 1.0 wt % of other components (SnO2);
[0027] (2) The glass obtained in step (1) is crystallized to obtain microcrystalline glass. The crystallization treatment is divided into two stages. The temperature of the first stage is 680°C and the time is 4 hours. The temperature of the second stage is 940°C and the time is 2 hours. After the crystallization treatment, annealing treatment is required. The annealing treatment temperature is 678°C and the time is 4 hours.
[0028] The microcrystalline glass prepared by the above method mainly consists of a glass matrix and crystal particles dispersed therein in a dendrite-like distribution, wherein the crystal particles consist of cordierite crystal particles, tetragonal zirconia crystal particles and zinc spinel crystal particles; the Mohs hardness of the microcrystalline glass is 7.6; the microcrystalline glass with a thickness of 0.5 mm is not broken after being impacted by a steel ball weighing 50 g and falling freely from a height of 1.5 m; the maximum light transmittance of the transparent microcrystalline glass with a thickness of 4 mm at a wavelength of 400 to 800 nanometers is 92%; the expansion coefficient α of the microcrystalline glass at a temperature of 30°C is 36*10 -7 / ℃.
[0029] Example 2
[0030] A method for preparing glass-ceramics comprises the following steps:
[0031] (1) melting the mixture at a temperature of 1666° C. for 9.5 hours and then casting or pressing the mixture to obtain ordinary glass, wherein the mixture consists of 48 wt % SiO2, 29 wt % Al2O3, 5.2 wt % MgO, 3 wt % ZnO, 4.7 wt % ZrO2, 0.1 wt % Y2O3, 0.2 wt % Sb2O3, 7 wt % BaO, 2 wt % La2O3 and 0.8 wt % of other components (SnO2);
[0032] (2) The glass obtained in step (1) is crystallized to obtain microcrystalline glass. The crystallization treatment is divided into two stages. The temperature of the first stage is 700°C and the time is 2.4 hours. The temperature of the second stage is 950°C and the time is 1.5 hours. After the crystallization treatment, annealing treatment is required. The annealing treatment temperature is 600°C and the time is 5 hours.
[0033] The microcrystalline glass prepared by the above method mainly consists of a glass matrix and crystal particles dispersed therein in a dendrite-like distribution, wherein the crystal particles consist of cordierite crystal particles, tetragonal zirconia crystal particles and zinc spinel crystal particles; the Mohs hardness of the microcrystalline glass is 7.3; the microcrystalline glass with a thickness of 0.5 mm is not broken after being impacted by a steel ball weighing 50 g and falling freely from a height of 1.5 m; the maximum light transmittance of the transparent microcrystalline glass with a thickness of 4 mm at a wavelength of 400 to 800 nanometers is 91%; the expansion coefficient α of the microcrystalline glass at a temperature of 30°C is 35*10 -7 / ℃.
[0034] Example 3
[0035] A method for preparing glass-ceramics comprises the following steps:
[0036] (1) melting a mixture at a temperature of 1684° C. for 10 hours and then casting or pressing the mixture to obtain ordinary glass, wherein the mixture consists of 48.4 wt % SiO2, 23.9 wt % Al2O3, 2 wt % MgO, 6.6 wt % ZnO, 8.8 wt % ZrO2, 5 wt % B2O3, 0.8 wt % Y2O3, 0.1 wt % Sb2O3, 4.1 wt % BaO, 0.2 wt % La2O3 and 0.1 wt % of other components (SnO2);
[0037] (2) The glass obtained in step (1) is crystallized to obtain microcrystalline glass. The crystallization treatment is divided into two stages. The temperature of the first stage is 780°C and the time is 1 hour. The temperature of the second stage is 980°C and the time is 1 hour. After the crystallization treatment, annealing treatment is required. The annealing treatment temperature is 700°C and the time is 5 hours.
[0038] The microcrystalline glass prepared by the above method mainly consists of a glass matrix and crystal particles dispersed therein in a dendrite-like distribution, wherein the crystal particles consist of cordierite crystal particles, tetragonal zirconia crystal particles and zinc spinel crystal particles; the Mohs hardness of the microcrystalline glass is 7.2; the microcrystalline glass with a thickness of 0.5 mm is not broken after being impacted by a steel ball weighing 50 g and falling freely from a height of 1.5 m; the maximum light transmittance of the transparent microcrystalline glass with a thickness of 4 mm at a wavelength of 400 to 800 nanometers is 80%; the expansion coefficient α of the microcrystalline glass at a temperature of 30°C is 34*10 -7 / ℃.
[0039] Example 4
[0040] A method for preparing glass-ceramics comprises the following steps:
[0041] (1) melting a mixture at a temperature of 1690° C. for 9.8 hours and then casting or pressing the mixture to obtain ordinary glass, wherein the mixture consists of 60 wt % SiO2, 22 wt % Al2O3, 2 wt % MgO, 7.5 wt % ZnO, 5.6 wt % ZrO2, 0.8 wt % B2O3, 1 wt % Y2O3, 0.2 wt % Sb2O3, 0.7 wt % La2O3 and 0.2 wt % of other components (SnO2);
[0042] (2) The glass obtained in step (1) is crystallized to obtain microcrystalline glass. The crystallization treatment is divided into two stages. The temperature of the first stage is 750°C and the time is 2.4 hours. The temperature of the second stage is 945°C and the time is 3 hours. After the crystallization treatment, annealing treatment is required. The annealing treatment temperature is 676°C and the time is 5 hours.
[0043] The microcrystalline glass prepared by the above method mainly consists of a glass matrix and crystal particles dispersed therein in a dendrite-like distribution, wherein the crystal particles consist of cordierite crystal particles, tetragonal zirconia crystal particles and zinc spinel crystal particles; the Mohs hardness of the microcrystalline glass is 7.0; the microcrystalline glass with a thickness of 0.5 mm is not broken after being impacted by a steel ball weighing 50 g and falling freely from a height of 1.5 m; the maximum light transmittance of the transparent microcrystalline glass with a thickness of 4 mm at a wavelength of 400 to 800 nanometers is 90%; the expansion coefficient α of the microcrystalline glass at a temperature of 30°C is 35.6*10 -7 / ℃.
[0044] Example 5
[0045] A method for preparing glass-ceramics comprises the following steps:
[0046] (1) melting a mixture at a temperature of 1680° C. for 12 hours and then casting or pressing the mixture to obtain ordinary glass, wherein the mixture consists of 41 wt % SiO2, 25 wt % Al2O3, 2.6 wt % MgO, 7.9 wt % ZnO, 8.2 wt % ZrO2, 1.2 wt % B2O3, 0.3 wt % Y2O3, 0.5 wt % Sb2O3, 10 wt % BaO, 2 wt % La2O3 and 1.3 wt % of other components (TiO2 and SnO2 in a mass ratio of 1:0.3);
[0047] (2) The glass obtained in step (1) is crystallized to obtain microcrystalline glass. The crystallization treatment is divided into two stages. The temperature of the first stage is 700°C and the time is 3 hours. The temperature of the second stage is 955°C and the time is 2 hours. After the crystallization treatment, annealing treatment is required at a temperature of 658°C.
[0048] The microcrystalline glass prepared by the above method mainly consists of a glass matrix and crystal particles dispersed therein in a dendrite-like distribution, wherein the crystal particles consist of cordierite crystal particles, tetragonal zirconia crystal particles and zinc spinel crystal particles; the Mohs hardness of the microcrystalline glass is 7.5; the microcrystalline glass with a thickness of 0.5 mm is not broken after being impacted by a steel ball weighing 50 g and falling freely from a height of 1.5 m; the maximum light transmittance of the transparent microcrystalline glass with a thickness of 4 mm at a wavelength of 400 to 800 nanometers is 90%; the expansion coefficient α of the microcrystalline glass at a temperature of 30°C is 35*10 -7 / ℃.
[0049] Example 6
[0050] A method for preparing glass-ceramics comprises the following steps:
[0051] (1) melting a mixture at a temperature of 1700° C. for 10.7 hours and then casting or pressing to obtain ordinary glass, wherein the mixture consists of 40 wt % SiO2, 32 wt % Al2O3, 3.2 wt % MgO, 10 wt % ZnO, 10 wt % ZrO2, 1.4 wt % B2O3, 0.8 wt % Y2O3, 0.2 wt % Sb2O3, 1.2 wt % BaO, 0.8 wt % La2O3 and 0.4 wt % of other components (SnO2 and AgO in a mass ratio of 3:1);
[0052] (2) The glass obtained in step (1) is crystallized to obtain microcrystalline glass. The crystallization treatment is divided into two stages. The temperature of the first stage is 720°C and the time is 2 hours. The temperature of the second stage is 980°C and the time is 2 hours. After the crystallization treatment, annealing treatment is required. The annealing treatment temperature is 680°C and the time is 5 hours.
[0053] The microcrystalline glass prepared by the above method mainly consists of a glass matrix and crystal particles dispersed therein in a dendrite-like distribution, wherein the crystal particles consist of cordierite crystal particles, tetragonal zirconia crystal particles and zinc spinel crystal particles; the Mohs hardness of the microcrystalline glass is 7.8; the microcrystalline glass with a thickness of 0.5 mm is not broken after being impacted by a steel ball weighing 50 g and falling freely from a height of 1.5 m; the maximum light transmittance of the transparent microcrystalline glass with a thickness of 4 mm at a wavelength of 400 to 800 nanometers is 83%; the expansion coefficient α of the microcrystalline glass at a temperature of 30°C is 35.2*10 -7 / ℃.
[0054] Example 7
[0055] A method for preparing glass-ceramics comprises the following steps:
[0056] (1) melting a mixture at a temperature of 1688° C. for 8 hours and then casting or pressing the mixture to obtain ordinary glass, wherein the mixture consists of 60 wt % SiO2, 22 wt % Al2O3, 4.5 wt % MgO, 3 wt % ZnO, 4 wt % ZrO2, 4.5 wt % BaO, 0.8 wt % La2O3 and 1.2 wt % of other components (TiO2 and SnO2 in a mass ratio of 1:0.2);
[0057] (2) The glass obtained in step (1) is crystallized to obtain microcrystalline glass. The crystallization treatment is divided into two stages. The temperature of the first stage is 725°C and the time is 3 hours. The temperature of the second stage is 954°C and the time is 3.5 hours. After the crystallization treatment, annealing treatment is required. The annealing treatment temperature is 647°C and the time is 5 hours.
[0058] The microcrystalline glass prepared by the above method mainly consists of a glass matrix and crystal particles dispersed therein in a dendrite-like distribution, wherein the crystal particles consist of cordierite crystal particles, tetragonal zirconia crystal particles and zinc spinel crystal particles; the Mohs hardness of the microcrystalline glass is 6.8; the microcrystalline glass with a thickness of 0.5 mm is not broken after being impacted by a steel ball weighing 50 g and falling freely from a height of 1.5 m; the maximum light transmittance of the transparent microcrystalline glass with a thickness of 4 mm at a wavelength of 400 to 800 nanometers is 89%; the expansion coefficient α of the microcrystalline glass at a temperature of 30°C is 35.6*10 -7 / ℃.
[0059] Example 8
[0060] A method for preparing glass-ceramics comprises the following steps:
[0061] (1) melting a mixture at a temperature of 1677° C. for 8.9 hours and then casting or pressing the mixture to obtain ordinary glass, wherein the mixture consists of 41.1 wt % SiO2, 23.5 wt % Al2O3, 2.7 wt % MgO, 6.8 wt % ZnO, 6.6 wt % ZrO2, 5 wt % B2O3, 1 wt % Y2O3, 0.8 wt % Sb2O3, 10 wt % BaO, 2 wt % La2O3 and 0.5 wt % of other components (TiO2 and SnO2 in a mass ratio of 3:2);
[0062] (2) The glass obtained in step (1) is crystallized to obtain microcrystalline glass. The crystallization treatment is divided into two stages. The temperature of the first stage is 715°C and the time is 2 hours. The temperature of the second stage is 920°C and the time is 2 hours. After the crystallization treatment, annealing treatment is required. The annealing treatment temperature is 688°C and the time is 5 hours.
[0063] The microcrystalline glass prepared by the above method mainly consists of a glass matrix and crystal particles dispersed therein in a dendrite-like distribution, wherein the crystal particles consist of cordierite crystal particles, tetragonal zirconia crystal particles and zinc spinel crystal particles; the Mohs hardness of the microcrystalline glass is 7.0; the microcrystalline glass with a thickness of 0.5 mm is not broken after being impacted by a steel ball weighing 50 g and falling freely from a height of 1.5 m; the maximum light transmittance of the transparent microcrystalline glass with a thickness of 4 mm at a wavelength of 400 to 800 nanometers is 92%; the expansion coefficient α of the microcrystalline glass at a temperature of 30°C is 35*10 -7 / ℃.
Claims
1. A method for preparing glass-ceramics, characterized in that: The mixture is cast into glass and then crystallized to obtain microcrystalline glass, wherein the mixture consists of 40-60wt% SiO2, 22-32wt% Al2O3, 2-9wt% MgO, 3-10wt% ZnO, 4-10wt% ZrO2, 0-5wt% B2O3, 0.1-1wt% Y2O3, 0.1-0.8wt% Sb2O3, 0-10wt% BaO, 0.2-2wt% La2O3 and other components with a content of less than 1.5wt%; the casting process is: the mixture is melted at a temperature of more than 1658°C for more than 8 hours and then cast or pressed into shape; the crystallization treatment is divided into two stages, the temperature of the first stage is 680-780°C, the time is 1-4h, and the temperature of the second stage is 920-980°C, the time is 1-3.5h; after the crystallization treatment, annealing treatment is performed at a temperature of 600-700°C; The other components are 1.0wt%, 0.8wt%, 0.1wt% or 0.2wt% SnO2; or a total amount of 1.3wt% TiO2 and SnO2, and the mass ratio of TiO2 to SnO2 is 1:0.3; or a total amount of 0.4wt% SnO2 and AgO, and the mass ratio of SnO2 to AgO is 3:1; or a total amount of 1.2wt% TiO2 and SnO2, and the mass ratio of TiO2 to SnO2 is 1:0.2; or a total amount of 0.5wt% TiO2 and SnO2, and the mass ratio of TiO2 to SnO2 is 3:2; The microcrystalline glass is mainly composed of a glass matrix and crystal particles dispersed therein in a dendritic distribution, and the crystal particles are composed of cordierite crystal particles, tetragonal zirconia crystal particles and galvanneal crystal particles; The Mohs hardness of glass-ceramics is 6.8~7.8; a 0.5mm thick glass-ceramics does not break after being hit by a 50g steel ball falling freely from a height of 1.5m; The maximum light transmittance of the transparent microcrystalline glass with a thickness of 4 mm is 80-92%, and the wavelength of the light is 400-800 nanometers.
2. The method for preparing glass-ceramics according to claim 1, characterized in that: The expansion coefficient of glass-ceramics at 30°C is 34*10 -7 ~36*10 -7 / ℃.
Citation Information
Patent Citations
High-crystallinity sodium nepheline transparent glass-ceramics and preparation method thereof
CN109608047A
clear crystallized glass
JP2691263B2
Microcrystal glass tube and preparation method thereof
CN101857373A
Powder for glass-ceramic dry refractory material
CN102712541A
Microcrystalline glass and substrate thereof
CN109867447A